Managing virtual teams for open innovation in Global Business Services industry. Issue 6 (5th February 2018) - Wei, Lee Heng; Thurasamy, Ramayah; Popa, Simona
Abstract : Purpose: The purpose of this paper is to investigate the impact of human dimensions, team climates, and technological features on Global Virtual Team (GVT) performance in the Malaysian Global Business Services (GBS) industry. Attention has also been paid to examine the moderating effect of team diversity and the extent of virtuality on GVT performance. Design/methodology/approach: Data were collected using structured questionnaire and tested using partial least square – structural equation modelling. The authors collected 263 sample and the assessment of reflective measurement models, structural model, reliability and validity were conducted subsequently. Findings: This paper found that team climates like team cohesion, team confidence, and team knowledge, skills, and abilities demonstrated different impact on the human dimensions which include trust and creativity. It will then subsequently affect GVTs' performance. Besides, team diversity which comprised of three major components that include age diversity, functional diversity, and attitudes/values diversity was found to moderate the relationships between the antecedents and consequent. In spite of that, the extent of virtuality was found to have no moderating effects on the relationships between the team creativity and trust and perceived team performance. Originality/value: As nowadays an increasing number of firms are becoming global, inquiring into GVTs efficient management is of crucial importance for successful implementation of open innovation practices, while GBS companies could represent the most suitable setting to examine the GVT's underlying principles. This paper integrates adaptive structuration theory with input-mediator-output-input model to provide a holistic study on GVTs' performance. In addition, this study also illustrated how the extent of virtually can be measured quantitatively.